2018
DOI: 10.1177/0038040718784603
|View full text |Cite
|
Sign up to set email alerts
|

A Downward Spiral? Childhood Suspension and the Path to Juvenile Arrest

Abstract: There is growing concern that suspensions trigger a ''downward spiral,'' redirecting children's trajectories away from school success and toward police contact. The current study tests this possibility, analyzing whether and in what ways childhood suspensions increase children's risk for juvenile arrests. Combining 15 years of data from the Fragile Families and Child Wellbeing Study with contextual information on neighborhoods and schools, I find that suspensions disproportionately affect children already endu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 59 publications
(60 reference statements)
7
116
0
1
Order By: Relevance
“…In this work, I extend the results of prior research on the consequences of excessive crime control for social exclusion and inequality by focusing on school suspension, which many have suggested is a precursor to criminal justice involvement (Hirschfield, ; Kupchik, ; Mittleman, ; Mowen & Brent, ; Ramey, ). Moreover, I aim to advance knowledge of the prevalence and outcomes of suspension in rural schools.…”
Section: Study Contributionsmentioning
confidence: 84%
See 2 more Smart Citations
“…In this work, I extend the results of prior research on the consequences of excessive crime control for social exclusion and inequality by focusing on school suspension, which many have suggested is a precursor to criminal justice involvement (Hirschfield, ; Kupchik, ; Mittleman, ; Mowen & Brent, ; Ramey, ). Moreover, I aim to advance knowledge of the prevalence and outcomes of suspension in rural schools.…”
Section: Study Contributionsmentioning
confidence: 84%
“…Reform efforts have led to recent declines in some states (Loveless, ), but overall rates are still high, particularly for disadvantaged and racial minority students, not because juvenile crime rates are high but because suspension is often in response to minor misbehavior like classroom disruptions and attendance problems (Kupchik, ; Morris & Perry, ; Skiba et al., ). This is problematic because in a growing body of research, scholars have suggested that suspension may be harmful for child and adolescent development (Cuellar & Markowitz, ; Jacobsen, Pace, & Ramirez, ; Mittleman, ; Morris & Perry, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research connects school punishment experiences to weaker bonds to school (Way, ); lower self‐esteem (Wolf & Kupchik, ); poor academic performance (Lacoe & Steinberg, ); and a failure to complete high school (Peguero & Bracy, ). These factors increase the likelihood that punished children will be involved with the criminal justice system during adolescence and adulthood (Mittleman, ; Ramey, ). Indeed, Scholars argue that this early exposure to the juvenile justice system initiates a “school‐to‐prison pipeline” in which some American children are pushed into the criminal justice system through criminalized school discipline and exclusionary school punishment (Hirschfield, ; Kim et al, ; Mittleman, ; Rios, ).…”
Section: Conceptualizing Criminalized Child Social Controlmentioning
confidence: 99%
“…"magna cum laude"). In the worst-case-scenario, they lead to a student's expulsion, the longterm consequences of which have been described as a "school-to-prison pipeline" (Kim, Losen, and Hewitt 2010;Mittleman 2018;Welch and Payne 2018). This definitional power extends far beyond the realm of education, into the world of literature (Franssen and Kuipers 2013), fashion (Mears 2010), business (Khurana 2002), and as we will see below, sports.…”
Section: Talent Is Whatever Is So Definedmentioning
confidence: 99%